Study on the Thicknesses and the Girths of Tendoachilles of Human Cadavers: Study in a Medical College - Nahar, Lutfun; Seraji, Ahmad; Rahman, Md Shofiur; Ahsanullah, Md Redwan (Journal of Shaheed Suhrawardy Medical College, 2020)
Study on the Thicknesses and the Girths of Tendoachilles of Human Cadavers. Background: Tendoachilles is the chief planter flexor of the ankle joint. It provides elastic energy storage in walking and running. The present study was planned to collect data to find out possible variations of thickness and girth between right and left leg of both male and female. Materials and methods: A cross sectional analytical type of study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka, from July 2013 to June 2014. The data was collected from both right and left tendoachilles of 60 human cadaver taken from Anatomy Department of different Government and Nongovernment Medical Colleges in Dhaka city. After dissection thickness and girth of tendoachilles was measured and recorded. Results: Among 60 human cadaver, 30 are male and 30 are female. The mean thickness of tendoachilles was greater in right leg than in left leg at its junction with gastrocnemius in male, (P<0.001) at the level of 4 cm above its junction with calcaneus and at the level of its junction with calcaneus in both male and female. No significant difference was observed in the measurement of thickness of right and left tendoachilles at the level of its junction with gastrocnemius in female. Mean girth of tendoachilles was greater in right leg than in left leg at its junction with gastrocnemius, at the level of 4 cm above its junction with calcaneus and at the level of its junction with calcaneus in both male and female. Conclusions: The present study revealed that thickness and girth of tendoachilles was greater in right leg than in left leg which were statistically significant. The difference in thickness and girth can be useful during repair of rupture tendon by orthopaedic and plastic surgeon. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 124-129